Examining Green Product Attributes and Healthy Lifestyle Orientation in Shaping Consumer Trust Toward Healthy Instant Food Brands - Devangga Putra Adhitya Pratama; Nur Hidayah; Heny Musfidah; Ardhita Eko Ginanjar (CV Pena Jaya Pers, 2025)
Purpose: This study examines the role of green product attributes and healthy lifestyle orientation in shaping consumer trust toward healthy instant food brands in East Java and Bali. Design/methodology/approach: A quantitative research design was employed using a survey method. Data were collected from 193 consumers in East Java and Bali and analyzed using validity tests, reliability tests, and multiple linear regression analysis with a five-point Likert scale. Findings: The results indicate that green product attributes and healthy lifestyle orientation have positive and significant effects on consumer trust, both partially and simultaneously. Research limitations/implications: This study is limited by its sample size and geographical focus on Java–Bali, which may restrict generalizability. Practical implications: The findings suggest that healthy instant food brands should emphasize credible green product attributes and align brand values with consumers’ healthy lifestyles to strengthen trust. Originality/value: This study positions consumer trust as a central outcome by integrating signaling theory, trust theory, and value congruence theory in the context of healthy instant food brands.